Massive Gastric Hemorrhage due to Dieulafoy’s Lesion in a Preterm Neonate: A Case Report and Literature Review of the Lesion in Neonates - Christos Salakos; Panayiota Kafritsa; Yvelise de Verney; Ariadni Sageorgi; Nick Zavras (Case Reports in Pediatrics)
Dieulafoy’s lesion is an extremely rare cause of upper gastrointestinal bleeding in the neonatal age group. Till now, only 6 cases of Dieulafoy’s lesion in neonatal period have been reported in the international literature. Herein, we report an extremely rare case of Dieulafoy’s lesion in a preterm neonate.